3D printed field-deployable microfluidic systems for the separation and assay of Pu in nuclear forensics. Issue 23 (15th September 2022) - Glennon, Kevin J.; Valdovinos, Hector F.; Parsons-Davis, Tashi; Shusterman, Jennifer A.; Servis, Anna G.; Moody, Kenton J.; Gharibyan, Narek
Abstract : Pu is separated from excess U and isotopically assayed using our novel microfluidic platform designed to miniaturize traditional laboratory techniques into a field-deployable system for rapid nuclear forensics in post-detonation nuclear scenarios. Abstract : A compact field-deployable microfluidic system has been developed to improve timelines for the rapid analysis of debris in post-detonation nuclear forensics. We used a high-resolution 3D printer to miniaturize typical laboratory-based procedures into a fieldable platform. Microfluidic half-modules were produced for the purification of Pu from excess U, along with a portable alpha chamber for the following isotopic analysis of the Pu stream. A porous PTFE membrane is soaked with a hydrophobic tributyl phosphate (TBP) solution and is placed between two half-modules; separation is performed as a liquid–liquid extraction in an extraction channel across this membrane, where the forward and back-extractions occur within one complete module. Following separation, a 100 μL sampling of the Pu-bearing stream is injected into a small-footprint 3D printed alpha chamber for isotopic assay via alpha spectrometry as part of an online process. In this first demonstration of microfluidic separation coupled with online alpha spectrometry, high extraction yields have been obtained for Pu (98.9 ± 4.0)% and U (97.5 ± 2.5)%. The process uses less than 800 μL of solution with separation chemistry complete within 45 minutes and subsequent alpha spectrometry initiating 25 minutes after separation.